TCR-T cell therapy for solid tumors: challenges and emerging solutions - He, Wanjun; Cui, Kai; Farooq, Muhammad Asad; Huang, Na; Zhu, Songshan; Jiang, Dan; Zhang, Xiqian; Chen, Jian; Liu, Yinxia; Xu, Guangxian (Frontiers in Pharmacology, 2025)
With the use of T cell receptor T cells (TCR-T cells) and chimeric antigen receptor T cells (CAR-T cells), T-cell immunotherapy for cancer has advanced significantly in recent years. CAR-T cell therapy has demonstrated extraordinary success when used to treat hematologic malignancies. Nevertheless, there are several barriers that prevent this achievement from being applied to solid tumors, such as challenges with tumor targeting and inadequate transit and adaption of genetically modified T-cells, especially in unfavorable tumor microenvironments The deficiencies of CAR-T cell therapy in the treatment of solid tumors are compensated for by TCR-T cells, which have a stronger homing ability to initiate intracellular commands, 90% of the proteins can be used as developmental targets, and they can recognize target antigens more broadly. As a result, TCR-T cells may be more effective in treating solid tumors. In this review, we discussed the structure of TCR-T and have outlined the drawbacks of TCR-T in cancer therapy, and suggested potential remedies. This review is crucial in understanding the current state and future potential of TCR-T cell therapy. We emphasize how important it is to use combinatorial approaches, combining new combinations of various emerging strategies with over-the-counter therapies designed for TCR-T, to increase the anti-tumor efficacy of TCR-T inside the TME and maximize treatment safety, especially when it comes to solid tumor immunotherapies.